A Mediterranean Diet and Low-Fat Vegan Diet to Improve Body Weight and Cardiometabolic Risk Factors: A Randomized, Cross-over Trial. Issue 2 (17th February 2022) - Barnard, Neal D.; Alwarith, Jihad; Rembert, Emilie; Brandon, Liz; Nguyen, Minh; Goergen, Andrea; Horne, Taylor; do Nascimento, Gabriel F.; Lakkadi, Kundanika; Tura, Andrea; Holubkov, Richard; Kahleova, Hana
Abstract: Objective: Evidence suggests that both Mediterranean and vegan diets improve body weight and cardiometabolic risk factors, but their relative efficacy has not been compared in a randomized trial. Methods: In a randomized crossover trial, 62 overweight adults were randomly assigned to a Mediterranean or vegan diet for a 16-week period. Body weight, plasma lipids, blood pressure, and body composition (dual X-ray absorptiometry) were measured. Secondary measures included insulin resistance (Homeostasis Model Assessment, HOMA-IR), oral glucose insulin sensitivity (OGIS), and predicted insulin sensitivity (PREDIM) indices. Thereafter, participants were asked to return to their baseline diets for 4 weeks, after which they began the opposite diet for 16 weeks. The same parameters were measured before and after this 2 nd 16-week period. Results: Overall net weight changes were 0.0 (Mediterranean) and −6.0 kg (vegan), (treatment effect −6.0 kg [95% CI −7.5 to −4.5]; p  < 0.001). HOMA-IR decreased and OGIS increased on the vegan diet with no significant change on the Mediterranean diet (treatment effect −0.7 [95% CI, −1.8 to +0.4]; p  = 0.21; and +35.8 mL/min/m 2 [95% CI, +13.2 to +58.3]; p = 0.003, respectively). PREDIM did not change significantly in either group. Among participants with no medication changes, total and LDL-cholesterol decreased 18.7 mg/dL (0.5 mmol/L) and 15.3 mg/dL (0.4 mmol/L), respectively, on the vegan diet, compared with no significant change on the Mediterranean diet (treatment effect −15.6 [-24.6 to −6.6]; p = 0.001 and −14.8 [-23.5 to −6.2]; p = 0.001, respectively); systolic and diastolic blood pressure decreased 9.3 and 7.3 mmHg on the Mediterranean diet, compared with 3.4 and 4.1 mmHg on the vegan diet (treatment effect +5.9 [95% CI +1.0 to +10.9]; p = 0.02; and +1.8 [95% CI −4.6 to +8.1]; p = 0.58, respectively). Conclusions: A low-fat vegan diet improved body weight, lipid concentrations, and insulin sensitivity, both from baseline and compared with a Mediterranean diet. Blood pressure decreased on both diets, more on the Mediterranean diet. Clinical trial registration: ClinicalTrials.gov number, NCT03698955 https://clinicaltrials.gov/ct2/show/NCT03698955?term=NCT03698955&draw=2&rank=1